Rare Earths-Schiff Base Complexes: A Potentiometric Study - Chondhekar, T.K. (Asian Journal of Chemistry, 2010)
Stability constants of lanthanide chelates of Schiff bases derived from 5-chloro-2-hydroxy acetophenone and p-toluidine and m-toluidine have been determined at 25º, 35º and 50º ± 0.02ºC potentiometrically in 60% ethanol-water medium and 0.1 M (NaClO4) ionic strength. The lanthanides form 1 : 1 and 1 : 2 chelates and the trend in log K values show a break at gadolinium. Thermodynamic functions obtained revealed that the 1 : 1 chelates were enthalpy and entropy stabilized and 1 : 2 chelates showed predominance of entropy effect.